Challenges and Opportunities in Digital Technology Adoption for Government in Indonesia - Wijaya, Indra Dharma (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
The adoption of digital technology in government sectors has become a critical aspect of improving public services and governance in Indonesia. However, its implementation faces several challenges, including infrastructure limitations, human resource capabilities, and regulatory issues. This study aims to explore the challenges and opportunities in adopting digital technology within the context of Indonesian governance. Using qualitative research methods, data were gathered through interviews with government officials, policy makers, and technology experts, as well as document analysis. The findings reveal significant barriers, such as uneven technological infrastructure across regions, limited digital literacy among civil servants, and unclear regulatory frameworks. On the other hand, the study also identifies opportunities, including the potential for enhancing citizen engagement, improving service delivery, and promoting transparency in governance. The research concludes that overcoming these challenges requires strategic policy interventions, capacity building, and stronger collaboration between government entities and technology providers.